“No Escalation of Treatment” Designations - Batten, Jason N.; Blythe, Jacob A.; Wieten, Sarah E.; Dzeng, Elizabeth; Kruse, Katherine E.; Cotler, Miriam P.; Porter-Williamson, Karin; Kayser, Joshua B.; Harman, Stephanie M.; Magnus, David (Chest, 2023)
No Escalation of Treatment (NoET) designations are used in ICUs internationally to limit treatment for critically ill patients. However, they are the subject of debate in the literature and have not been qualitatively studied. How do physicians understand and perceive NoET designations, especially regarding their usefulness and associated challenges? What mechanisms do hospitals provide to facilitate the use of NoET designations? Qualitative study at seven US hospitals, employing semistructured interviews with 30 physicians and review of relevant institutional records (eg, hospital policies, screenshots of ordering menus in the electronic health record). At all hospitals, participants reported the use of NoET designations, which were understood to mean that providers should withhold new or higher-intensity interventions (“escalations”) but not withdraw ongoing interventions. Three hospitals provided a specific mechanism for designating a patient as NoET (eg, a DNR/Do Not Escalate code status order); at the remaining hospitals, a variety of informal methods (eg, verbal hand-offs) were used. We identified five functions of NoET designations: (1) Defining an intermediate point of treatment limitation, (2) helping physicians navigate prearrest clinical decompensations, (3) helping surrogate decision-makers transition toward comfort care, (4) preventing patient harm from invasive measures, and (5) conserving critical care resources. Across hospitals, participants reported implementation challenges related to the ambiguity in meaning of NoET designations. Despite ongoing debate, NoET designations are used in a varied sample of hospitals and are perceived as having multiple functions, suggesting they may fulfill an important need in the care of critically ill patients, especially at the end of life. The use of NoET designations can be improved through the implementation of a formal mechanism that encourages consistency across providers and clarifies the meaning of “escalation” for each patient. [Display omitted]